Effects of different irrigation levels on the quality of Trincadeira grapes – Mediterranean conditions - Pirata, Madalena (2015)
This work reports the research on Trincadeira grape vine subject to three increasing levels of irrigation: i) non irrigation, ii) farmer irrigation or iii) full irrigation. During grape’s maturation, berry size and quality parameters were analyzed. Only in September all analysed parameters were significantly different: non-irrigated plants had smaller berries and lower brix, anthocyanins and polyphenols than irrigated ones.